3,5-Bis(arylidene)-4-piperidones as potential dengue protease inhibitors - Osman, Hasnah; Idris, Nor Hashima; Kamarulzaman, Ezatul Ezleen; A. Wahab, Habibah; Hassan, Mohd. Zaheen (Elsevier, 2017)
Dengue is a severe mosquito-borne viral in fection causing half a million deaths annually. Dengue virusNS2B/NS3 protease is a validated target for anti-dengue drug design. A series of hitherto unreported 3,5-bis(arylidene)-4-piperidones analogues 4a–4j were synthesized and screened in silico against DENV2 NS2B/NS3 protease to elucidate their binding mechanism and orientation around the active sites. Results were validated through an in vitro DENV2 NS2B/NS3 protease assay using a fluorogenic Boc-Gly-Arg-Arg-AMC substrate. Nitro derivatives of 3,5-is(arylidene)-4-piperidones(4e and 4j) merged as promising lead molecules for novel protease inhibitors with an IC50 of 15.22 and 16.23 umoI/L, respectively, compared to the standard, panduratin A, having IC50 of 57.28 umoI/L.